Thoracic Aortic Graft Infections Secondary to Propionibacterium Species: Two Cases and Review of the Literature. (August 2016) - Pineda, Danielle M.; Tyagi, Samuel; Dougherty, Matthew J.; Troutman, Douglas A.; Calligaro, Keith D.
Aortic graft infections are a rare occurrence, most commonly secondary to gram-positive organisms ( Staphylococcus and Streptococcus species). We present 2 cases of thoracic aortic graft infections secondary to anaerobic bacteria, Propionibacterium species. The first case, a 40-year-old male, was found to have an anastomotic aneurysm at the distal anastomosis of a previous thoracoabdominal aneurysm repair. During the open repair of his anastomotic aneurysm, the original graft was not incorporated and cultures later speciated Propionibacterium acnes . The second case is a 44-year-old male with a history of abdominal aortic coarctation that was repaired with a thoracic aorta to aortic bifurcation graft as a child who presented with flank pain and was found on imaging to have fluid around his bypass graft. His operating room (OR) cultures also grew out Propionibacterium species. Both patients were treated with graft excision, revascularization, and long-term antibiotics. Anaerobic bacteria are a rare cause of aortic graft infections. Upon review of the literature, these are the first 2 cases of thoracic aortic graft infections secondary to Propionibacterium species. The cultures for both patients took almost a week to speciate, highlighting the importance of following cultures long term. Anaerobic bacteria should be recognized as a cause of latent graft infections.